2013
DOI: 10.1016/j.apnu.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Research With Adolescents With Schizophrenia and Their Families

Abstract: The purpose of this study is to present our experiences of conducting a randomized clinical trial of a self-management intervention for adolescents with schizophrenia and their families. Challenges and strategies of recruiting subjects; engaging families in self-management intervention; tailoring interventions for this population were discussed. Participants' comments on their experience were presented. Adolescents and their families are poorly prepared to manage schizophrenia; therefore psychosocial intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Limitations of this preliminary report also include the small sample size as it limited the power to detect significant differences. Participants with recent‐onset schizophrenia are not easy to recruit (Lee & Schepp, 2013; Robinson, 2011); however, future trials should make efforts to increase sample size to produce more robust findings. Moreover, the absence of a follow‐up period did not allow to understand whether the training effects are durable.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this preliminary report also include the small sample size as it limited the power to detect significant differences. Participants with recent‐onset schizophrenia are not easy to recruit (Lee & Schepp, 2013; Robinson, 2011); however, future trials should make efforts to increase sample size to produce more robust findings. Moreover, the absence of a follow‐up period did not allow to understand whether the training effects are durable.…”
Section: Discussionmentioning
confidence: 99%
“…Although our target sample size was 40, we were able to recruit only 22 participants from outpatient clinics through the use of recruitment flyers. Involving health care providers at outpatient clinics in participant recruitment activities may also be an important strategy to ensure targeted enrollment rates (H. Lee & Schepp, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they would prefer to manage their weight without having to participate in face-to-face treatment programs because of geography, lack of transportation (The National Alliance on Mental Illness, 2008), or the stigma attached to accessing such resources (H. Lee & Schepp, 2013). Consequently, people with SMI need interventions that not only motivate them to engage in recommended amounts of PA but also allow them ease of access to PA.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, Killikelly et al [36] found, in their systematic review, that participants’ adherence to Web- and mobile-based interventions ranged between 28% and 100%. Indeed, persons with schizophrenia can be a challenging target group for study recruitment in general [30,37-40]. The aim of this study was to test the feasibility and acceptability of a Web-based educational intervention among persons with schizophrenia using a quasi-experimental study design and to report preliminary evidence of its impact on self-efficacy, self-esteem, knowledge level about schizophrenia, and illness cognition.…”
Section: Introductionmentioning
confidence: 99%